Conservation and distribution of the DRACH motif for potential m6A sites in avian leukosis virus subgroup J - Ji, Jun; Mu, Xinhao; Xu, Shuqi; Xu, Xin; Zhang, Zhibin; Yao, Lunguang; Xie, Qingmei; Bi, Yingzuo (Frontiers in Veterinary Science, 2024)
N6-methyladenosine (m6A) methylation is an internal post-transcriptional modification that has been linked to viral multiplication and pathogenicity. To elucidate the conservation patterns of potential 5′-DRACH-3′ motifs in avian leukosis virus subgroup J (ALV-J), 149 ALV-J strains (139 isolates from China; ALV-J prototype HPRS-103 from the UK; and 9 strains from the USA, Russia, India, and Pakistan) available in GenBank before December 2023 were retrieved. According to the prediction results of the SRAMP web-server, these ALV-J genomes contained potential DRACH motifs, with the total number ranging from 43 to 64, which were not determined based on the isolation region and time. Conservative analysis suggested that 37 motifs exhibited a conservation of >80%, including 17 motifs with a grading above “high confidence.” Although these motifs were distributed in the U5 region of LTRs and major coding regions, they were enriched in the coding regions of p27, p68, p32, and gp85. The most common m6A-motif sequence of the DRACH motif in the ALV-J genome was GGACU. The RNA secondary structure of each conserved motif predicted by SRAMP and RNAstructure web-server was mainly of two types—A–U pair (21/37) and hairpin loop (16/37)—based on the core adenosine. Considering the systematic comparative analysis performed in this study, future thorough biochemical research is warranted to determine the role of m6A modification during the replication and infection of ALV-J. These conservation and distribution analysis of the DRACH motif for potential m6A sites in ALV-J would provide a foundation for the future intervention of ALV-J infection and m6A modification.